The impact of adverse childhood experiences on depression in old age: evidence from China - Liu, Ziqiong; Cao, Enlin; Wei, Hua (Frontiers in Psychiatry, 2025)
ObjectiveThis study explores the links between negative childhood experiences and depression in older adults, focusing on how pensions and offspring support influence the relationship between adverse childhood experiences (ACEs) and the mental health outcomes of the elderly.MethodsData were obtained from the 2016, 2018, and 2020 China Longitudinal Aging Social Survey (CLASS). We used the ordinary least squares (OLS) method and moderation tests to analyze depression health outcomes.ResultsOlder adults with ACEs had worse mental health outcomes than those without ACEs. The ACEs of medical deficiency, parental absence, and hunger during childhood manifested as higher depression scores in old age. The heterogeneity regression results show that medical deficiency and hunger experiences have a more significant impact on the depression of elderly individuals in urban areas. In contrast, early experiences of parental absence have a greater effect on the depression of elderly individuals in rural areas. Regression results for moderating effects indicate that children’s support can effectively alleviate the impact of adverse childhood experiences on the depression status of the elderly; however, pensions and the number of friends do not play a positive moderating role.ConclusionACEs, pension, and offspring support were independently associated with older adults’ mental health problems, and the combination of ACEs and low offspring support was the most significant predictor of adverse health outcomes in old age, controlling for adult sociodemographic indicators. Enhancing supportive relationships between children and older adults may buffer the negative effects of early adversities on older adult well-being.